Undergraduate Students' Perception Towards The Use of Mendeley Referencing System on Students' Thesis Writing - Santosa, Made Hery; Adnyani, Luh Diah Surya; Amarwati, Luh Rika (Journal of Education Research and Evaluation, 2021)
This study aimed at investigating undergraduate students’ perception towards the use of Mendeley referencing system on students’ thesis writing and describe challenges faced by undergraduate students when using Mendeley on thesis writing. This study used mixed-method research design, particularly explanatory sequential mixed-method. 100 undergraduate students of English Language Education, Ganesha Univesity of Education involved in this study. The instruments used in this study are questionnaire and interview. Questionnaire consisted of 16 statements and interview consisted of 12 questions. The result of questionnaire showed very positive perception which means the students strongly agreed that Mendeley usage on students’ thesis writing is highly useful. Moreover, the interview result showed the challenges came up when the students connecting Mendeley to Ms. Word and the meta data of articles and books could not generated automatically. Thus, the students need to re-check and input the meta data manually.